2018
DOI: 10.1002/aoc.4620
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of nanocomposites from cationic polyacrylamide and modified carbon black: Application as flocculants for oily sludge suspension

Abstract: Carbon black was modified using various liquid-phase oxidation methods (modified carbon black = m-CB, m = (1, 2, 3): 1, sulfuric acid/potassium permanganate method; 2, nitric acid method; 3, hydrogen peroxide method). With acetone-ethylene glycol as initiator, dimethyldiallylammonium chloride (DMDAAC) and acrylamide (AM) as monomer, cationic polyacrylamide (CPAM) was prepared by UV excitation of the monomer. The m-CB/CPAM nanocomposites were synthesized using a hydrothermal method. The factors that affected th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The results showed that the flocculant had obvious advantages in treating oil-bearing wastewater. Similar studies, for example, the study in 2019 by Tian et al [129], synthesized P(DMC-AM) on the modified composite nanomaterials by reacting activated carbon with DMC and AM and used it to conduct flocculation of an oil-sludge suspension to analyze the flocculation mechanism. The results showed that the material not only had a remarkable flocculation effect, but also realized the flocculation of sludge particles by adsorption bridging and charge neutralization in acidic and alkaline conditions.…”
Section: Common Polymersmentioning
confidence: 88%
“…The results showed that the flocculant had obvious advantages in treating oil-bearing wastewater. Similar studies, for example, the study in 2019 by Tian et al [129], synthesized P(DMC-AM) on the modified composite nanomaterials by reacting activated carbon with DMC and AM and used it to conduct flocculation of an oil-sludge suspension to analyze the flocculation mechanism. The results showed that the material not only had a remarkable flocculation effect, but also realized the flocculation of sludge particles by adsorption bridging and charge neutralization in acidic and alkaline conditions.…”
Section: Common Polymersmentioning
confidence: 88%
“…Modified carbon black/cationic polyacrylamide (m-CB/CPAM) nanocomposites were synthesised and used byTian et al (2018) as flocculants for oil sludge suspension treatment. Several factors such as the total monomer concentration, the dosage of the complex initiator, the mass ratio ofacrylamide (AM) to dimethyldiallylammonium chloride (DMDAAC) [mAM:mDMDAAC] and the UV irradiation time were found to affect the molecular weight of CPAM.…”
mentioning
confidence: 99%